Europe is the greatest thing in North America : Delmore Schwartz's 'International Consciousness' - Runchman, Alexander Herbert (Trinity College (Dublin, Ireland). School of English, 2012)
My introduction considers the way in which Schwartz interprets the American Dream in a seminal essay about Ernest Hemingway, suggesting this as a framework within which to consider Schwartz’s work in general. I then offer a critical overview, refuting James Atlas’s simplistic presentation of Schwartz as a ‘confessional’ poet, delineating my own literary principles, and going on to argue that an appreciation of Schwartz’s dream logic is a fruitful way into analysing his method of composition.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin